(untitled) (Bangladesh Journal of Medicine, 2024)
Copper Sulfate known as a powerful oxidizing agent and it can lead to widespread cellular damage, depending upon the dose ingested. The systemic effects of poisoning are seen primarily on red blood cells, gastrointestinal system, kidneys and cardiovascular system. The ingestion of poison can be lethal in severe cases. We reported the case of a 16-year-old girl who presented to the emergency department after ingestion of an unknown amount of copper sulfate 3 days earlier. On admission to the hospital, she had upper abdominal pain, vomiting and red colored urine with a normal serum copper level. She underwent symptomatic treatment and was monitored for 3 days. The outcome was favorable, and she had no signs and symptoms of organ failure. Bangladesh J Medicine 2024; 35: 114-117